TV commercials : how to make them, or, how big is the boat? - Cury, Ivan (Elsevier, 2005)
Understanding how commercials are made is the key to doing it right. This descriptive book is a step-by-step guide on the mechanics of creating a commercial from a production perspective. Making commercials on all types of budgets is addressed. There is material describing the roles and dynamics of the key players: the producer/director, agency, and client. This book outlines the requirements of each group so that everyone can understand and appreciate each other's needs.